Analysis of the Influence of Environmental Concern, Theory of Planned Behavior, and Theory of Reasoned Action on Purchase Intention: A Conceptual Paper - Fanisa Tris Wandani; Arry Widodo; Nurafni Rubiyanti; Anita Silvianita (PT FORMOSA CENDEKIA GLOBAL, 2024)
The cosmetics industry is one of the industries that is currently an important necessity in people's daily lives. The cosmetics industry is an important industry for the economy. The green cosmetics industry in Indonesia has great growth potential. This study aims to validate the Theory of Reasoned Action (TRA) and Theory of Planned Behavior (TPB) models in predicting public attitudes towards purchasing intentions for environmentally friendly cosmetic products. Environmental concern, attitude, subjective norms, and perceived behavioral control (PBC), are expected to influence consumer decisions to buy green cosmetic products in Indonesia. This study's sample technique was nonprobability sampling. This is a sample approach that is chosen based on subjective assessment. Purposive sampling is the method utilized. The research sample consisted of customers who had used and purchased green cosmetic products in Indonesia who were then analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) technique in this research